Making research integral to home care services. Issue 5 (September 2015) - Lang, Ariella; Shamian, Judith; Goodwin, Sharon
Home care is the fastest growing segment of the Canadian healthcare system, yet research on patient safety has been conducted predominantly in institutional settings. This is a case example of how Victorian Order of Nurses Canada, a national not-for-profit home and community care provider, embedded a nurse researcher to create an environment in which health services research flourished. This model strategically propelled important issues such as home care safety on to the national research and policy agendas and helped leverage change in multiple levels of the healthcare system. This is a call to action for building partnerships to have a researcher as an integral team member in organizations providing home care services.